Top 10 palliative care research priorities in France: a 3-step, mixed-methods protocol (AXEPRO study) - Stéphane Sanchez; Guillaume Economos; Fiona Ecarnot; Cecile Barbaret; Raphaëlle Habert-Dantigny; Héloïse Rouze; Doan Huynh; Roseline Huynh; Caroline Tête; Martin Julier-Costes; Valérie Amouroux-Gorsse; Isabelle Lavault; et al. (BMJ Open)
Introduction As one means to avoid waste in research investment, involving patients as full partners in research has become increasingly frequent. There is clearly a low level of investment in palliative care research. Following the guidance from the James Lind Alliance and the UK public consultation (‘Palliative and End of Life Care Research Priorities Project’), we developed a 3-step protocol aimed at prioritising 10 unanswered questions in palliative care (PC) research in France, from the viewpoint of patients, volunteers, healthcare professionals and family caregivers.Methods and analysis To identify unanswered questions in PC (stage 1), an unstructured questionnaire will be used. This questionnaire will be tested on patients and healthcare professionals and modified, if necessary, before being made available online for a period of 6 months. A multidisciplinary steering committee including board-certified PC physicians, methodologists, nurses, a sociologist, an anthropologist and an information specialist will analyse the data collected in order to delete duplicate questions, do a thematic and population classification of the responses, modify questions using the PICO (patient problem, intervention, comparison and outcome) format and perform a literature review on each question to identify any relevant systematic review.Ethics and dissemination We expect the results to have wide-ranging benefits, for example, by prompting investment in the 10 prioritised research questions. There are also potential benefits for patients and caregivers, by including them as partners in future research. Regarding the current bill being examined by the government planning to legalise euthanasia and assisted suicide in France, this study will provide new insights into how patients and caregivers are prioritising those themes. The major benefit of this study is to involve patients and family caregivers as partners in PC research. They will be consulted and their choices will be valuable resources and may prompt researchers to focus on different topics. In view of the limited funding available, PC research needs to prioritise major issues and raise its visibility.The second stage of the study is the first-round prioritisation using a fixed format questionnaire, which will last 4 months. The third stage will consist of reaching a consensus regarding the top 10 unanswered questions in PC research, using the nominal group technique. A secondary objective during this third step is to study the reasons for the prioritisation.